The Development of Digital Textbook Using eXe Format to Elevate Learning Effectiveness in History Instruction at The Second Grade of Senior High School - Kayan Swastika; Mohammad Na'im (International Journal of Education and Humanities, 2022)
This research aims to produce a digital textbook using eXe format (E-Learning XHTML Editor) in the History subject of the second grade of senior high school in a chapter focusing on “Dutch Military Aggression.” The textbook has been proven valid and feasible to increase students’ engagement in History learning. In addition, it aims to encourage students’ independent learning and help them reach minimum passing criteria (henceforth MPC), which implies the goal of improved learning effectiveness. The development of digital textbooks using eXe formats applied the ASSURE development model proposed by Sharon Smaldino et al. The digital textbook development consisted of six stages, namely (1) analyzing learners’ characteristics, (2) stating performance objectives, (3) selecting instructional methods, media, and materials, (4) utilizing the materials, (5) engaging learning in instruction, and (6) evaluating and revising. The results of the data analysis have drawn several conclusions. First, the digital textbook has been proven effective in helping satisfy students’ learning needs; 2). the digital textbook is proven an attractive learning resource for learning Indonesian History and, therefore a valuable resource to increase student interest in learning Indonesian History; 3) the digital textbook aids in increasing the effectiveness of instruction on Indonesian History, and 4) The digital textbook can be one of the references to help students better learn Indonesian History